Investor Protection in Indonesia: Financial Ratios as Early Warning Indicators - Enggar Sukma Kinanthi; Sukmawati Sukamulja (Journal of Economics, Business, and Accountancy Ventura, 2025)
The Indonesian government aims to enhance public engagement in the capital market by strengthening investor protection and financial literacy through the establishment of a Watchlist Board. This study identifies the most effective financial ratios for distinguishing between the performance of LQ45 and Watchlist Board firms. Using discriminant analysis, the research examines a sample of 43 firms from the LQ45 index and 43 firms from the Watchlist Board between 2020 and 2022. The findings reveal four key financial ratios with strong differentiating power: Total Asset Growth, Return on Assets (ROA), Operating Cash Flow (OCF) to Current Liabilities, and OCF to Total Liabilities. Additionally, the study develops a predictive model that can forecast company performance and serve as an early warning system for investors. Building on prior research in this area, the results highlight the critical role of profitability, efficient resource allocation, and robust corporate governance in fostering financial stability and safeguarding investor interests. This study not only provides a practical predictive model but also offers valuable insights for interpreting these financial ratios, particularly in the context of investor protection within emerging markets, such as Indonesia.